An annotated catalogue of Indian Lasiocampidae (Lasiocampoidea, Lepidoptera) - Joshi, Rahul; Singh, Navneet; Ahmad, Jalil (Zootaxa, 2023)
We catalogue 100 species (including nominotypic subspecies) and five subspecies in 35 genera of Lasiocampinae, Lasiocampidae from India. This represents 5% of the 1,952 species of Global Lasiocampidae. Information on types (locality and depository), synonymy, diversity and distribution in different biogeographic zones of India alongwith global records, contribution of various authors on Indian Lasiocampidae is provided. Apart from seven doubtful records, clarifications are given as remarks wherever needed. Additionally, Streblote alpherakyi (Christoph, 1885) and Odontocraspis collieri Zolotuhin & Witt, 2000a are reported for the first time from India.